Analytical and experimental study of a motion amplification damper for improving energy dissipation capacity of precast post-tensioned structural systems - Kulaksizoğlu, Ahmet Ata. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Seismic design approach for structures is rapidly evolving towards low-damage design, with the aim of limiting structural damage in members in addition to providing sufficient strength. Precast post-tensioned concrete is a construction system which is very efficient in limiting seismic structural damage because of two phenomena. The earthquake resistance of the structure is provided by connecting precast members with post-tensioning tendons, which are designed to remain elastic subjected to seismic effects. In addition, the gap opening mechanism allows the structural damage to occur locally in specially designed joints. These aspects unique to precast post-tensioned concrete, however, reduce the hysteretic energy dissipation capacity of the structures, which in other systems exist due to plastic hinging of structural members. To enhance energy dissipation capacity of this system, various external dampers have been proposed in the literature. Majority of these dampers are metallic yielding or translational friction dampers, which work with the principle of relative translational displacement. In this study, an external damper which works with rotational friction mechanism due to relative rotation between friction surfaces is proposed. The contribution of damper to the energy dissipation capacity is increased by amplifying relative rotations between surfaces by way of geometric disposition of the damper mechanism. Analytical and experimental studies were conducted and it was concluded that the proposed damper had significant contribution to energy dissipation capacity of precast post-tensioned systems and novel aspects that distinguishes it from previously proposed dampers.
Keywords: Earthquake resistant design.; Energy dissipation.